PasSport4life: A trainee sport psychologist's perspective on developing a resilience-based life skills program. Issue 3 (1st September 2016) - Cox, Hamish; Neil, Rich; Oliver, Jon; Hanton, Sheldon
ABSTRACT: The growing field of sport-based youth development has explored the role of coaches in fostering athletes' lifelong skills to deal with stressors and challenges they encounter as they transition into adulthood. However, the contribution of sport psychologists in implementing programs has received little attention and could provide a beneficial catalyst in facilitating youth development given their training and expertise. In addition, the use of resilience-related life skills could support adolescents in overcoming adversity beyond sport. Therefore, the purpose of this article is to provide a narrative on the experiences of a trainee sport psychologist in designing and delivering a resilience-based life skills program.